Beyond Learner-Centered Practice: Adult Education, Power, and Society - Cervero, Ronald; Wilson, Arthur (Canadian Journal for the Study of Adult Education, 1999)
At the heart of practice in most conceptions of adult education is the adult learner whose needs for learning, once uncovered, can be met through the effective design of educational programs. There has been increasing dissatisfaction with this view of practice, however, as adult education has moved to a central position in the constitution of social, cultural, and economic life. Learner-centeredness is a naive position that does not come close to approximating the political and ethical dilemmas nor the contradictions and the possibilities for action in this new situation for adult education. In place of learner-centeredness we suggest that adult education in the next millennium must be seen as a struggle for the distribution of knowledge and power in society. At the heart of practice, then, should be a vision linking adult education, power, and society. Résumé La plupart des conceptions andragogiques placent l'apprenant au centre de leur préoccupation pratique. Elles considèrent que les besoins d'apprentissage de celui-ci, une fois identifiés, peuvent être rencontrés grace au design de programmes éducatifs. Or, cette conception s'est butée à une insatisfaction croissante alors que la pratique andragogique s'établissait au cœur la vie sociale, culturelle et économique. La notion d'intervention centrée sur l'apprenant est naïve et ne rend pas compte des dilemmes politiques et éthiques, ni des contradictions et des possibilités d'action dans le nouveau contexte. À l'aube du nouveau millénaire, nous suggérons plutôt une représentation de l'andragogie qui étaye la lutte pour une distribution équitable du savoir et dupouvoir dans la société. La pratique devient alors tributaire d'une vision liant andragogie, pouvoir et société.